Unified fields : science and literary form - Rogers, Janine, 1968- (McGill-Queen's University Press, 2014)
Through a series of close readings of poetry and prose, Unified Fields demonstrates that formal structures in literature can relate to scientific concepts through their essential interpretive functions.--Provided by publisher.